Pyrolysis of contaminated PS single-layer and LDPE/PET multi-layer waste plastic packaging to optimise the production of oil for fuel applications - Van der Westhuizen, Salomie (Stellenbosch : Stellenbosch University., 2020)
Thesis (MEng)--Stellenbosch University, 2020.